Strengthening Creative Activity through Extracurricular Projects and Exhibitions - Rahimova Gulhayo Qahramonovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines the pedagogical significance of extracurricular projects and art exhibitions in enhancing students’ creative activity within visual arts education. It explores how out-of-class artistic initiatives—such as workshops, competitions, and thematic exhibitions—contribute to the development of imagination, self-expression, and teamwork among learners. The study highlights that extracurricular activities not only supplement classroom learning but also create conditions for artistic independence, emotional engagement, and the discovery of individual talent. Practical recommendations are provided for organizing creative projects and exhibitions that motivate students and promote cultural values through art.